2015
DOI: 10.1007/s13762-015-0759-4
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of emissions and fuel consumption in a compression ignition engine using nanoparticles

Abstract: In this paper, the effect of adding nanoparticles on the performance characteristics of diesel engine was investigated. Up to now, several metallic nanoadditives including cerium and aluminum have been applied in this area. However, the possibility of using some other metals or modification in the additive structures as well as improving or changing the basic fluid is among factors manifesting a broad scope of work in this area. For this purpose, the silver nanoparticles were used as additives to the net diese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…Compared with the M10, the M10A100's in-cylinder pressure and peak heat release rate have been increased by a maximum of 3.6% and 7.12%. This is because the adhesion bond between fuel molecules and Al2O3 nanoparticles produces denser droplets and ligaments, which improves the atomization effect of methanol-based nanofluid fuel injection [13] . In addition, Al2O3 particles can improve the thermal conductivity of fuel, and accelerate the evaporation and mixing of fuel and air [14] .…”
Section: Combustion Characteristicsmentioning
confidence: 99%
“…Compared with the M10, the M10A100's in-cylinder pressure and peak heat release rate have been increased by a maximum of 3.6% and 7.12%. This is because the adhesion bond between fuel molecules and Al2O3 nanoparticles produces denser droplets and ligaments, which improves the atomization effect of methanol-based nanofluid fuel injection [13] . In addition, Al2O3 particles can improve the thermal conductivity of fuel, and accelerate the evaporation and mixing of fuel and air [14] .…”
Section: Combustion Characteristicsmentioning
confidence: 99%
“…Nanocatalysts are improving the efficiency of many conversion processes in petroleum processing industries [92]. Moreover, car fuel consumption can be reduced by adding metallic nanoparticles to fuel, which ensure more efficient combustion [93]. Already described CNTs have proved effective as a low-temperature adsorbents for carbon dioxide (CO 2 ) capture from power plant flue gas [94].…”
Section: Energeticsmentioning
confidence: 99%
“…Nanofluid addition not helps to improve the thermal conductivity of the vehicle engine, but also helps to reduce pollutant emissions [75,76]. An experimental study [75] was performed by adding silver nanoparticles to pure diesel fuel.…”
Section: Nanotechnology Applications In Transportation Vehiclesmentioning
confidence: 99%
“…Nanofluid addition not helps to improve the thermal conductivity of the vehicle engine, but also helps to reduce pollutant emissions [75,76]. An experimental study [75] was performed by adding silver nanoparticles to pure diesel fuel. From the result evaluation, it was concluded that the inclusion of the nanomaterial greatly reduced the emission rates of NO x and CO by up to 13 and 20.5%, respectively [75].…”
Section: Nanotechnology Applications In Transportation Vehiclesmentioning
confidence: 99%
See 1 more Smart Citation